Influence of bone density on the cement fixation of femoral hip resurfacing components - Bitsch, Rudi G.; Jäger, Sebastian; Lürssen, Marcus; Loidolt, Travis; Schmalzried, Thomas P.; Clarius, Michael (Journal of orthopaedic research, 2010)
In clinical outcome studies, small component sizes, female gender, femoral shape, focal bone defects, bad bone quality, and biomechanics have been associated with failures of resurfacing arthroplasties. We used a well-established experimental setup and human bone specimens to analyze the effects of bone density on cement fixation of femoral hip resurfacing components. Thirty-one fresh frozen femora were prepared for resurfacing using the original instruments. ASR™ resurfacing prostheses were implanted after dual-energy X-ray densitometer scans. Real-time measurements of pressure and temperature during implantation, analyses of cement penetration, and measurements of micro motions under torque application were performed. The associations of bone density and measurement data were examined calculating regression lines and multiple correlation coefficients; acceptability was tested with ANOVA. We found significant relations between bone density and micro motion, cement penetration, cement mantle thickness, cement pressure, and interface temperature. Mean bone density of the femora was 0.82 ± 0.13 g/cm2, t-score was −0.7 ± 1.0, and mean micro motion between bone and femoral resurfacing component was 17.5 ± 9.1 µm/Nm. The regression line between bone density and micro motion was equal to −56.7 × bone density + 63.8, R = 0.815 (p < 0.001). Bone density scans are most helpful for patient selection in hip resurfacing, and a better bone quality leads to higher initial component stability. A sophisticated cementing technique is recommended to avoid vigorous impaction and incomplete seating, since increasing bone density also results in higher cement pressures, lower cement penetration, lower interface temperatures, and thicker cement mantles. © 2010 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 28:986-991, 2010
Gesehen am 08.02.2023